The Arctic Atmosphere : Sulphur and Trace Metals - Wadleigh, M. (Geoscience Canada, 1996)
Summary The atmosphere is the principal transport path to the Arctic of sulphur, toxic heavy metals and chlorinated organic compounds. One of the consequences of these pollutants is the winter phenomenon of arctic haze. Once a pollutant is emitted into the atmosphere, its transport to the Arctic is determined by the position of the polar front. In winter, the front expands to occupy a large fraction of the North American and Asian continents. Anthropogenic sulphur and metal input to the Arctic peaks in the winter half of the year and aerosol studies point to Eurasia as the major source region. By adding to these data, trace metal and other isotopic information indicative of particular sources {e.g., V, Pb,Zn), apportionment may become possible. Precipitation and lichen monitoring activities could provide useful additional information for characterizing change in the Arctic atmosphere.